Characteristics of edge pedestals in LHW and NBI heated H-mode plasmas on EAST. (28th July 2016) - Zang, Q.; Wang, T.; Liang, Y.; Sun, Y.; Chen, H.; Xiao, S.; Han, X.; Hu, A.; Hsieh, C.; Zhou, H.; Zhao, J.; Zhang, T.; et al.
Abstract: By using the recently developed Thomson scattering diagnostic, the pedestal structure of the H-mode with neutral beam injection (NBI) or/and lower hybrid wave (LHW) heating on EAST (Experimental Advanced Superconducting Tokamak) is analyzed in detail. We find that a higher ratio of the power of the NBI to the total power of the NBI and the lower hybrid wave (LHW) will produce a large and regular different edge-localized mode (ELM), and a lower ratio will produce a small and irregular ELM. The experiments show that the mean pedestal width has good correlation with β p, ped 0.5, The pedestal width appears to be wider than that on other similar machines, which could be due to lithium coating. However, it is difficult to draw any conclusion of correlation between ρ * and the pedestal width for limited ρ * variation and scattered distribution. It is also found that T e / ∇ T e is 2 cm, which is the same as the AUG (ASDEX Upgrade), DIII-D and JET (Joint European Torus) results.